Aligned ZnO nanorods synthesized by a simple hydrothermal reaction - Wei, A. (2012)
Zinc oxide (ZnO) nanorods were fabricated by a hydrothermal reaction in ammonia and zinc chloride solution without any surfactant at 95◦C in a sealed bottle. In the area near the solution surface, the product presented urchin-like arrays composed of needle-tipped nanorods with about 40 nm diameter. In the middle and the bottom of the solution, the ZnO nanorods grew vertically on the substrate and showed tapered and flat ends and bigger diameters of about 300–400 nm. The microstructure characterization of x-ray diffraction and high resolution transmission electron microscopy images demonstrated that all ZnO nanorods grew along the [0001] direction. The influence of the chemical reactions and the depth-dependent growth along various facets of ZnO are discussed.